2017
DOI: 10.1016/j.margeo.2016.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Submarine channel evolution, terrace development, and preservation of intra-channel thin-bedded turbidites: Mahin and Avon channels, offshore Nigeria

Abstract: 15Terraces on the modern seafloor are defined as topographically flat areas above the active 16 submarine channel thalweg but within the confines of the channel-belt. They have been 17 described from many modern submarine channels, but the controls on terrace distribution, 18 evolution and stacking patterns are not well understood. In this study, we describe the The surfaces defining the bases of the terrace bodies have been mapped along both channels 26 using high-resolution 3D seismic data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
70
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 66 publications
6
70
0
Order By: Relevance
“…This has a consequence for the likelihood of microplastic remobilization by subsequent turbidity currents, for sampling methodology (as most studies sample only the uppermost few centimeters of beds), as well as the availability of microplastics to ingestion by seafloor and/or burrowing fauna (Wright et al, 2013). In situations where a flow is constrained by topography (e.g., within a channel), the upper part of the overspilling flow will tend to concentrate particles that have a low settling velocity (e.g., Kane et al, 2007;Hansen et al, 2015Hansen et al, , 2017McArthur et al, 2017), making depositional areas such as levees more likely sites for microplastics accumulation. A summary of deep-marine gravity flow deposit types and likely microplastic distribution is presented in Figure 10.…”
Section: Gravity Flow Depositsmentioning
confidence: 99%
See 1 more Smart Citation
“…This has a consequence for the likelihood of microplastic remobilization by subsequent turbidity currents, for sampling methodology (as most studies sample only the uppermost few centimeters of beds), as well as the availability of microplastics to ingestion by seafloor and/or burrowing fauna (Wright et al, 2013). In situations where a flow is constrained by topography (e.g., within a channel), the upper part of the overspilling flow will tend to concentrate particles that have a low settling velocity (e.g., Kane et al, 2007;Hansen et al, 2015Hansen et al, , 2017McArthur et al, 2017), making depositional areas such as levees more likely sites for microplastics accumulation. A summary of deep-marine gravity flow deposit types and likely microplastic distribution is presented in Figure 10.…”
Section: Gravity Flow Depositsmentioning
confidence: 99%
“…Submarine channels are long-term conduits for sediment transport and extend from the canyon into the deeper basin, and terminate in lobe deposits beyond the channel mouth (Normark, 1970;Pickering et al, 1989;Mutti and Normark, 1991;Normark et al, 1997;Peakall et al, 2000;Jobe et al, 2015;Hansen et al, 2017). Channels may be bound at their margins by erosional surfaces or levees, or both (e.g., Clark and Pickering, 1996;Li P. et al, 2016).…”
Section: Submarine Channelsmentioning
confidence: 99%
“…Talling et al, 2015). Moreover, several studies have shown that quasi-linear submarine channel long profiles are common (e.g., Covault et al, 2011;Georgiopoulou and Cartwright, 2013;Hansen et al, 2016). For this reason, we prefer to evaluate submarine channel long profile and planform responses to a known deformation field and to deduce what this tells us about their time-integrated evolution and geometry rather than assuming a priori we know the steady-state concave form.…”
Section: Channel Response To Seabed Structuresmentioning
confidence: 99%
“…(), Gamboa and Alves (), Qin et al. () and Hansen, Janocko, Kane, and Kneller (). Detailed morphological analyses (Figure ) of sediment conduits were only performed on the 3‐D seismic data, whereas the 2‐D seismic lines were used for regional correlations of horizons and units (Figures a and a,c).…”
Section: Data and Approachmentioning
confidence: 99%